2015
DOI: 10.1021/es506063h
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Nitrogenous Disinfection Byproducts after Medium Pressure UV Water Treatment by Stable Isotope Labeling and High Resolution Mass Spectrometry

Abstract: Advanced oxidation processes are important barriers for organic micropollutants (e.g., pharmaceuticals, pesticides) in (drinking) water treatment. Studies indicate that medium pressure (MP) UV/H2O2 treatment leads to a positive response in Ames mutagenicity tests, which is then removed after granulated activated carbon (GAC) filtration. The formed potentially mutagenic substances were hitherto not identified and may result from the reaction of photolysis products of nitrate with (photolysis products of) natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 41 publications
1
50
0
Order By: Relevance
“…30 The combination of controlled laboratory experiments with real world monitoring often facilitates prioritization by adding new information. 31,32 For example, in lab experiments Kolkmann et al 31 traced mutagenic nitrogenous disinfection byproducts (N-DBPs) formed with reactive N species during UV drinking water treatment by adding 15 N-labeled nitrate.…”
Section: Challenges In Prioritizationmentioning
confidence: 99%
See 1 more Smart Citation
“…30 The combination of controlled laboratory experiments with real world monitoring often facilitates prioritization by adding new information. 31,32 For example, in lab experiments Kolkmann et al 31 traced mutagenic nitrogenous disinfection byproducts (N-DBPs) formed with reactive N species during UV drinking water treatment by adding 15 N-labeled nitrate.…”
Section: Challenges In Prioritizationmentioning
confidence: 99%
“…Experiment-driven Frequency, signal intensity of masses 14,33 Persistence 34 , elimination/formation 29 over process Component with characteristic isotope pattern (C, Cl, Br, N, O, S) 13,19,35 Reaction-based search of transformation products to link masses before and after treatment 30 Part of homologue series (mass difference, Kendrick mass defect) 13,36,37 Biological 28 , electrochemical 38 , oxidative 32 transformation product formation Suspect screening (looking for "known" or predicted chemicals without standard) 39,40 Reaction with isotopically-labelled reagents 31 Specific functional groups (MS/MS, derivatisation, neutral loss) 41,42 Effect-directed selection of masses in toxic fractions 43,44 Temporal or spatial profile over several samples 24,33 A second limitation is accounting for potential toxicity during prioritization. Approaches such as Effect-Directed Analysis use biological effect tests to prioritize chromatographic fractions with unknown components associated with specific toxic effects for identification.…”
Section: Data-drivenmentioning
confidence: 99%
“…Although UV disinfection of seawater is not as common as drinking water and wastewater treatment, UV/ TiO 2 had faster disinfection kinetics than only UV 254 light irradiation in a lab-scale experiment with synthetic seawater showing the effectiveness of photocatalytic treatment on seawater disinfection (Rubio et al, 2013). However, it has been shown that the presence of nitrate can lead to nitrogen incorporation into organic matter through nitrate photolysis (Kolkman et al, 2015;Thorn and Cox, 2012;Vione et al, 2001;Suzuki et al, 1987).…”
Section: Dbp Formation In Chlorinated Seawatermentioning
confidence: 99%
“…Recent technological advancements in chromatography and high resolution MS (HRMS) allows detection and tentative identification of compounds without the prior need of standards [1]. This 'non-target' analysis (NTA) approach is increasingly adopted to perform simultaneous screening of up to thousands of chemicals in the environment, such as finding new CEC [1][2][3][4][5][6], identifying chemical transformation (by)products [7][8][9][10][11][12] and identification of toxicants in the environment [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%